Adenosine 5'-phosphosulfate kinase from Penicillium chrysogenum. Purification and kinetic characterization - Renosto, F; Seubert, P A; Segel, I H (The Journal of biological chemistry, 1984)
Adenosine 5'-phosphosulfate (APS) kinase, the second enzyme in the pathway of inorganic sulfate assimilation, was purified to near homogeneity from mycelium of the filamentous fungus, Penicillium chrysogenum. The enzyme has a native molecular weight of 59,000-60,000 and is composed of two 30,000-dalton subunits. At 30 degrees C, pH 8.0 (0.1 M Tris-chloride buffer), 5.5 microM APS, 5 mM MgATP, 5 mM excess MgCl2, and “high” salt (70-150 mM (NH4)2SO4), the most highly purified preparation has a specific activity of 24.7 units X mg of protein-1 in the physiological direction of adenosine 3'-phosphate 5'-phosphosulfate (PAPS) formation. This activity is nearly 100-fold higher than that of any previously purified preparation of APS kinase. APS kinase is subject to potent substrate inhibition by APS. In the absence of added salt, the initial velocity at 5 mM MgATP plus 5 mM Mg2+ is maximal at about 1 microM APS and half-maximal at 0.2 and 4.4 microM APS. In the presence of 200 mM NaCl or 70-150 mM (NH4)2SO4, the optimum APS concentration shifts to 4-6 microM APS; the half-maximal values shift to 1-1.3 and 21-27 microM APS. The steady state kinetics of the reaction were investigated using a continuous spectrophotometric assay. The families of reciprocal plots in the range 0.25-5 mM MgATP and 0.8-5.1 microM APS are linear and intersect on the horizontal axis. Appropriate replots yield KmMgATP = 1.5 mM, KmAPS = 1.4 microM, and Vmax, = 38.7 units X mg of protein-1. Excess APS is an uncompetitive inhibitor with respect to MgATP (K1APS = 23 microM). PAPS, the product of the forward reaction, is also uncompetitive with MgATP. PAPS is not competitive with APS. In the reverse direction, the plots have the characteristics of a rapid equilibrium ordered sequence with MgADP adding before PAPS. The kinetic constants are KmPAPS = 8 microM, KiMgADP = 560 microM, and Vmaxr = 0.16 units X mg of protein-1. Iso-PAPS (the 2'-phosphate isomer of PAPS) is competitive with PAPS and uncompetitive with respect to MgADP (Ki = 6 microM). APS kinase is inactivated by phenylglyoxal, suggesting the involvement of an essential argininyl residue. MgATP or MgADP at 10 Ki protect against inactivation. APS or PAPS at 600 and 80 Km, respectively, are ineffective alone, but provide nearly complete protection in the presence of 0.1 Ki of MgADP or MgATP.